Research progress on the inhibition of oxidative stress by teriparatide in spinal cord injury - Ai, Gangtong; Xiong, Moliang; Deng, Liang; Zeng, Jihuan; Xiao, Qiang (Frontiers in Neurology, 2024)
Spinal cord injury (SCI) is currently a highly disabling disease, which poses serious harm to patients and their families. Due to the fact that primary SCI is caused by direct external force, current research on SCI mainly focuses on the treatment and prevention of secondary SCI. Oxidative stress is one of the important pathogenic mechanisms of SCI, and intervention of oxidative stress may be a potential treatment option for SCI. Teriparatide is a drug that regulates bone metabolism, and recent studies have found that it has the ability to counteract oxidative stress and is closely related to SCI. This article summarizes the main pathological mechanisms of oxidative stress in SCI, as well as the relationship between them with teriparatide, and explores the therapeutic potential of teriparatide in SCI.